Regulação das profissões de saúde na Índia - Lal, Dharmesh K. (2018)
Health workforce regulations are central to achieving health objectives, ensuring high and safe standards of healthcare. The health workforce regulation needs to ensure quality of education, infrastructure and continual maintenance of professionals' standards across all health professions. These measures also assure the public, other stakeholders, and practitioners that all the concerns about standards of the workforce will be addressed in transparent and consistent manner. Broadly the regulations consist of policy making, admission guidelines to the different health professional courses, defining and regulating education standards through controlling the qualifications and expertise of the faculty, teaching institutes required infrastructure, maintenance of a register, continuous upgradation and regular assessment of professional skills as well as monitoring the quackery-practice by unqualified people, investigating and dealing with problems in relation to the conduct, health or performance of registered practitioners. Healthcare in India is provided by a variety of groups with varying skill levels, across a range of systems of medicine both in the public and private sector and there are regulatory bodies for doctors, dentists, nurses and pharmacists. This paper presents Indias' Health Workforce Regulatory Model, identifying its main institutions and regulatory mechanisms.